Dosimetry evaluation of photon beam profile characteristics for different treatment parameters of quality assurance - Taghreed Ahmed Nghaimesh; Siham Sabah Abdullah; Hadeel Kamil Abdullah; Abdulrahman Mohammed Abdulbaqi (Journal of the Pakistan Medical Association, 2024)
Objective: To compare beam profiles of MatriXX scanning system and water phantom for different treatment parameters. Method: The cross-sectional study was conducted at Al-Amal National Hospital for Cancer Treatment, Baghdad, Iraq, from November 2020 to March 2021. Beam data for 6MV and 10MV photon beams generated from the linear accelerator was utilised at field sizes 20×20cm2, 15×15 cm2, 10×10cm2 and 5×5cm2 at depth 10 and source-to-skin distance 100cm. Data was obtained for both water phantom and MatriXX system. The dose distribution for the two systems were compared. Data was analysed using SPSS 24. Results: The 32 measures taken were all related to symmetry and flatness. Flatness data indicated that all measurements were within tolerance except for cross line plane variations in 10x10cm2 field size with 6MV energy (-3.81%) and 5x5cm2 field size with 10MV energy (-3.01).Symmetry data revealed all measurement differences were within tolerance. Conclusion: MatriXX system could also be used for routine photon profile measurements as a substitute for water phantom. Key Words: Water, Photons, Phantoms, Imaging.